ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS BELAJAR PADA TOPIK ARITMATIKA MENGGUNAKAN SOAL BERTINGKAT PADA SISWA SMP KELAS 9 - Septiana Pujianingsih; Julia Hanifah Ahza; Sherli Salsabila Adawiyah; Adam Higaf Kurniawan; Devi Akifana; Fadhilah Rahmawati (LINEAR: Journal of Mathematics Education, 2020)
In understanding the mathematical concepts each student has different abilities. It is influenced by various factors such as intelligence, emotional condition, environment, etc. This study aims to identify mathematical comprehension skills with a four-tier diagnostic test method. The subject of this study was a grade 1X student at SMP Negeri 4 Purworejo. This research uses descriptive qualitative method with case study strategy. In identifying mathematical comprehension skills with a four-tier diagnostic test method can be done by four stages namely: 1) question, 2) level of trust in the answer, 3) reason, and 4) level of trust in the reason. Based on the results of the study, data obtained from a four-level diagnostic test in the Arithmetic chapter showed that 71 students showed that students could solve problems (73.96%), 23 students showed students understood the problem (23.96%), 1 student showed that they could not understand the problem (1.04%), and 1 student showed that they could apply the concept (1.04%).